Short Proline-Rich Lipopeptide Potentiates Minocycline and Rifampin against Multidrug- and Extensively Drug-Resistant Pseudomonas aeruginosa - Domalaon, Ronald (Antimicrob Agents Chemother, 2018)
A series of 16 short proline-rich lipopeptides (SPRLPs) were constructed to mimic longer naturally existing proline-rich antimicrobial peptides. Antibacterial assessment revealed that lipopeptides containing hexadecanoic acid (C(16)) possess optimal antibacterial activity relative to others with shorter lipid components. SPRLPs were further evaluated for their potential to serve as adjuvants in combination with existing antibiotics to enhance antibacterial activity against drug-resistant Pseudomonas aeruginosa. Out of 16 prepared SPRLPs, C(12)-PRP was found to significantly potentiate the antibiotics minocycline and rifampin against multidrug- and extensively drug-resistant (MDR/XDR) P. aeruginosa clinical isolates. This nonhemolytic C(12)-PRP is comprised of the heptapeptide sequence PRPRPRP-NH(2) acylated to dodecanoic acid (C(12)) at the N terminus. The adjuvant potency of C(12)-PRP was apparent by its ability to reduce the MIC of minocycline and rifampin below their interpretative susceptibility breakpoints against MDR/XDR P. aeruginosa. An attempt to optimize C(12)-PRP through peptidomimetic modification was performed by replacing all l- to d-amino acids. C(12)-PRP demonstrated that it was amenable to optimization, since synergism with minocycline and rifampin were retained. Moreover, C(12)-PRP displayed no cytotoxicity against human liver carcinoma HepG2 and human embryonic kidney HEK-293 cell lines. Thus, the SPRLP C(12)-PRP is a lead adjuvant candidate that warrants further optimization. The discovery of agents that are able to resuscitate the activity of existing antibiotics against drug-resistant Gram-negative pathogens, especially P. aeruginosa, is of great clinical interest.